THE APPLICATION OF AUTHOWARE 7.0 MEDIA TO INCREASE STUDENTS’ LEARNING INTEREST ON CIRCULATION SYSTEM MATERIALS AT SMPN 2 KUTA BARO - Riska, Nur; Dewi, Cut Ratna; Hanim, Nafisah (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
ABSTRACTThe lack of variety in the using of learning media is one of the factors that causes students' low interest in learning. This is influenced by the less active role of students in the learning process. One of the effort to overcome this problem is by applying learning media that is appropriate to the learning material, that is learning media based on Macromedia Authoware 7.0. The aim of this research is to determine students' interest in learning after using Macromedia Authoware 7.0-based learning media on circulatory system material. This research uses the Pre-Experimental Design method with a One Group Pretest-Posttest design. The population and the sample in this study were 8th grades students at SMPN 2 Kuta Baro totaling 18 students. Sample selection was carried out by total sampling. Data collection techniques for student interest using questionnaires and observation sheets. Data analysis of student learning interest using the percentage formula. The results of the interest analysis at the first meeting showed a result of 58.3% with low criteria, then at the second meeting it was 79.98% with high criteria so that Ha was accepted and H0 was rejected. So it can be concluded that learning using media based on Macromedia Authoware 7.0 can increase students' interest in learning in 8th grades students at SMPN 2 Kuta Baro.